Seroimmunotyping of African swine fever virus - Sereda, Alexey D.; Namsrayn, Sanzhi; Balyshev, Vladimir M.; Vlasov, Mikhail E.; Sindryakova, Irina P.; Koltsova, Galina; Kolbasov, Denis V. (Frontiers in Microbiology, 2023)
The extreme genetic and immunobiological heterogeneity exhibited by the African swine fever virus (ASFV) has been a significant impediment in the development of an efficacious vaccine against this disease. Consequently, the lack of internationally accepted protocols for the laboratory evaluation of candidate vaccines has become a major concern within the scientific community. The formulation of such protocols necessitates the establishment of a consensus at the international level on methods for the determination of homologous and heterologous isolates/strains of ASFV. The present article provides a comprehensive description of biological techniques employed in the classification of ASFV by seroimmunotypes. These techniques involve a holistic evaluation of ASFV isolates/strains based on their antigenic properties as determined by the hemadsorption inhibiting test (HAdI) using type-specific sera and an immunological test (IT) conducted on pigs inoculated with attenuated strains. The article outlines the methods for setting up the HAdI test, an IT on pigs, and the processes involved in the acquisition of type-specific serums for the HAdI test. It is pertinent to note that the definitive classification of seroimmunotype can only be ascertained after conducting an IT on pigs. The findings from the HAdI test or the phylogenetic analysis of the EP402R gene should be considered preliminary in nature.